2020
DOI: 10.1038/s41467-020-18246-6
|View full text |Cite
|
Sign up to set email alerts
|

Pan-cancer study detects genetic risk variants and shared genetic basis in two large cohorts

Abstract: Deciphering the shared genetic basis of distinct cancers has the potential to elucidate carcinogenic mechanisms and inform broadly applicable risk assessment efforts. Here, we undertake genome-wide association studies (GWAS) and comprehensive evaluations of heritability and pleiotropy across 18 cancer types in two large, population-based cohorts: the UK Biobank (408,786 European ancestry individuals; 48,961 cancer cases) and the Kaiser Permanente Genetic Epidemiology Research on Adult Health and Aging cohorts … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
176
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 175 publications
(202 citation statements)
references
References 67 publications
13
176
0
Order By: Relevance
“…Cancer sites for which the PRS resulted in the largest gains in prediction performance included prostate, testicular, and thyroid cancers, as well as leukemia, and melanoma. This is consistent with high heritability estimates reported for these cancers in twin studies 14 and our analyses in the UK Biobank 15 . Modeling the PRS in addition to established risk factors yielded very modest improvements in risk discrimination for cancers of the lung, endometrium, bladder, oral cavity/pharynx, and kidney.…”
Section: Discussionsupporting
confidence: 92%
“…Cancer sites for which the PRS resulted in the largest gains in prediction performance included prostate, testicular, and thyroid cancers, as well as leukemia, and melanoma. This is consistent with high heritability estimates reported for these cancers in twin studies 14 and our analyses in the UK Biobank 15 . Modeling the PRS in addition to established risk factors yielded very modest improvements in risk discrimination for cancers of the lung, endometrium, bladder, oral cavity/pharynx, and kidney.…”
Section: Discussionsupporting
confidence: 92%
“…Overall, the results of our cross-cancer PRS analyses demonstrated unique patterns of pleiotropy relative to studies focused on array-based shared heritability or genetic correlations [28][29][30][31] . In GERA and the UK Biobank, our group previously found suggestive evidence of positive correlations between bladder and breast cancers, melanoma and testicular cancer, and prostate and thyroid cancers and negative correlations between endometrial and testicular cancers, lung cancer and melanoma, and NHL and prostate cancer 31 . These pairs did not surface in our cross-cancer PRS analyses in these same cohorts, except suggestive evidence of bidirectional positive associations between melanoma and testicular cancer.…”
Section: Discussionmentioning
confidence: 66%
“…Genome-wide association studies (GWAS) of individual cancer types have also identified loci associated with multiple cancer types, including 5p15 ( TERT-CLPTM1L) 3 , 6p21 (HLA complex) 4 , 5 , and 8q24 6 . Non-GWAS approaches have yielded further pleiotropic cancer risk variants 7 27 , and genetic correlation studies have identified cancer pairs with shared heritability 28 31 .…”
Section: Introductionmentioning
confidence: 99%
“…We explored pleiotropic associations between lead variants influencing antibody levels and several chronic diseases with known or hypothesized viral risk factors. Associations with selected cancers were obtained from a cancer pleiotropy meta-analysis of the UK Biobank and Genetic Epidemiology Research on Aging cohorts [ 27 ]. Summary statistics for the schizophrenia GWAS of 33,640 cases and 43,456 controls by Lam et al [ 28 ] were downloaded from the Psychiatric Genomics Consortium.…”
Section: Methodsmentioning
confidence: 99%